BETWEEN CRISES AND FRAGILE STABILITY: TURKIYE-ISRAEL AFFAIRS - Adisonmez, Umut Can; Oztig, Lacin Idil (TURKISH POLICY QUARTERLY, 2022)
Since the establishment of Israel, the Turkish-Israeli relations have been marked by continuous periods of swings - from crises to cooperation and back. This article aims to shed light on the turbulent bilateral ties by focusing on the role of the current Justice and Development Party (JDP) rule in Turkiye. In doing so, it firstly provides a background on the two countries' relations, covering the period between their foundational years and 2002. Secondly, it explores a series of significant crises against which the Turkish-Israeli relations reached an all-time low starting with the Operation Cast Lead in 2008. Given the recent developments unfolding in Turkiye's domestic sphere and its close geography, this work lastly assesses the impact of the Abraham Accords in 2020 on bilateral relations and speculates about the future trajectories.
Keywords: Government & Law